Wear rate of epoxy resin reinforced with multi walls carbon nanotubes - Hameed, Ayad Qabash (Iraqi Journal of Physics, 2019)
In this study, nanocomposites have been prepared by adding multiwall carbon nanotubes (MWCNTs) with weight ratios (0, 2, 3, 4, 5) wt% to epoxy resin. The samples were prepared by hand lay-up method. Influence of an applied load before and after immersion in sodium hydroxide (NaOH) of normality (0.3N) for (15 days) at laboratory temperature on wear rate of Ep/MWCNTs nanocomposites was studied. The results showed that wear rate increases with increasing the applied load for the as prepared and immersed samples and after immersion. It was also found that epoxy resin reinforced with MWCNTs has wear rate less than neat epoxy. The sample (Ep + 5wt% of MWCNTs) has lower wear rate. The immersion effect in base solution led to increase in wear rate values for all samples compared to natural condition.